2004
DOI: 10.1001/archderm.140.6.677
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Modeling of Narrowband UV-B Phototherapy for Vitiligo Using a Novel Quantitative Tool

Abstract: Background:There is currently no quantitative tool for evaluating vitiligo treatment response using parametric methods.Objective: To develop and apply a simple clinical tool, the Vitiligo Area Scoring Index (VASI), to model the response of vitiligo to narrowband UV-B (NB-UV-B) phototherapy using parametric tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
360
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(368 citation statements)
references
References 22 publications
3
360
1
4
Order By: Relevance
“…This study found that MKTP was an effective and well-tolerated procedure based on the objective scoring system for the assessment of repigmentation (Vitiligo Area Scoring Index). 40 Postoperatively, the treated area appears bright red, which lasts up to 2-3 weeks in dark-skinned patients and up to 6-12 weeks in light-skinned people. Repigmentation is observed as early as 3-4 weeks post-transplantation, with progression up to 6 months in skin types IV and V. In contrast, repigmentation begins about 8-12 weeks post-transplantation with progression up to 1 year in skin types II and III.…”
Section: Cultured and Noncultured Cellular Transplantation Methodsmentioning
confidence: 99%
“…This study found that MKTP was an effective and well-tolerated procedure based on the objective scoring system for the assessment of repigmentation (Vitiligo Area Scoring Index). 40 Postoperatively, the treated area appears bright red, which lasts up to 2-3 weeks in dark-skinned patients and up to 6-12 weeks in light-skinned people. Repigmentation is observed as early as 3-4 weeks post-transplantation, with progression up to 6 months in skin types IV and V. In contrast, repigmentation begins about 8-12 weeks post-transplantation with progression up to 1 year in skin types II and III.…”
Section: Cultured and Noncultured Cellular Transplantation Methodsmentioning
confidence: 99%
“…History of spontaneously repigmenting vitiligo was excluded from the study. There is currently no quantitative tool for evaluating vitiligo treatment response using parametric methods (Hamzavi et al 2004). Repigmentation may starts on the hair follicle(typical perifollicular) or starts as homogenous pigmentation from the periphery of the lesions (perilesional) (Baltas & Csoma 2002).…”
Section: Methodsmentioning
confidence: 99%
“…The Vitiligo Area Scoring Index (VASI) was used to evaluate treatment outcome 6 . The VASI is a quantitative method used to standardize treatment outcomes.…”
Section: Assessmentmentioning
confidence: 99%